Patterns of Neck Main Arteries Morphometry and Echocardiography Data - Maksud А. Khalilov; Andrey S. Moshkin; Lyubov V. Moshkina (Вестник рентгенологии и радиологии)
Objective: to compare the objective results of ultrasound imaging of neck main arteries with echocardiography data, to assess the correlation patterns between the morphological characteristics of the structures.Material and methods. A total of 244 volunteers (who had no signs of significant hemodynamic disorders, surgical interventions on the heart and studied vessels) were examined, who underwent ultrasound imaging of the carotid arteries and echocardiography. All studies were performed using a single technique with an assessment of the diameters of common carotid artery (CCA), internal carotid artery (ICA), external carotid artery (ECA), vertebral arteries (VA), as well as intima-media complex (IMC). The echographic characteristics of the aortic wall, aortic and mitral valves were considered. The data obtained were grouped and subjected to statistical analysis.Results. Based on the diagnostic data obtained by echocardiography, eight groups were formed: (1) with signs of changes in the aorta; (2) with changes at the level of the aorta and aortic valve; (3) with changes in the aorta and mitral valve; (4) with changes in the aortic and mitral valves; (5) without signs of changes in the aorta, aortic and mitral valves; (6) with changes only in the aortic valve; (7) with changes only in the mitral valve; (8) with changes only at the level of the aortic and mitral valves. When assessing the differences between pairs of groups in cases of diagnosis of structural changes in the aortic walls and valvular heart apparatus, the indicators differed slightly, more often for IMC value. There were differences for ICA diameter when comparing Groups 1 and 4. Morphometric parameters of VA in cases of diagnosed changes did not reflect significant differences. The largest CCA diameter (5.8±0.7 mm) was noted in combination with changes in the aortic wall and heart valves. The smallest CCA diameter (5.0± 0.3) mm was in Group 6. The largest ICA (4.6±0.4 mm) and ECA (3.6±0.4) diameters were with changes in the mitral valve. The smallest ICA diameter (4.1±0.4 mm) was observed with changes only in the aortic walls. The smallest values for ECA and VA diameters were 2.8 mm, combined with changes in the aortic valve only. The most pronounced differences were obtained when comparing data in the absence of significant changes in the aortic walls and heart valves for CCA, VA, and ECA IMC.Conclusion. The presented results expand our understanding of the individual features of neck main arteries, accompanying changes in the aortic walls and valvular apparatus of the heart.